Confocal and concentric annular elliptic light guides and their modal characteristics - Verma C.B.P.; Singh U.K.; Singh V.B.; Singh II O.N. (My University, 2025)
We consider two annular elliptic light guides, one whose guiding region cross-section is bounded by two confocal ellipses (CFEG) and the other whose guiding region is bounded by two concentric ellipses (CEG). Using Goell's point matching method we obtain the characteristic equations and dispersion curves for these waveguides. When the dispersion curves are compared, it is found that they are steeper in the case of CFEG than in the case of CEG. It is also found that the cutoff value of the lowest order mode for the CFEG is greater than that for the CEG. This means that the CFEG supports fewer modes than the CEG.